Analysis of Strontium and Lead Isotopic Ratios in Environmental Matrices Using ICP-MS - Voica, Cezara; Iordache, Andreea Maria (Geography, Earth Science and Environment: Research Highlights Vol. 8, 2025)
Determining the 87Sr/86Sr isotopic ratio in environmental samples by inductively coupled plasma quadrupole mass spectrometry (ICP-Q-MS) can be performed to explore this ratio as a tracer of the pollution source. The isotopic ratios of Sr in environmental samples have strong regional variations usually controlled by the underlying geology. This fact allows the creation of methodologies by which these elements can be used as traceability indices to determine the origin of metals. Lead isotopic ratios are often monitored to identify the isotopic fingerprint and as tracers to differentiate natural and anthropogenic lead. This work presents the 87Sr/86Sr and 206Pb/207Pb isotope compositions of 40 samples of river waters and sediments from regions of Romania using the ICP-MS technique. This method makes it possible to determine isotopic compositions precisely, which is important for researching processes like environmental change, geological origins, and pollution tracing. Studying isotope ratios can reveal important information about natural versus man-made influences in a variety of environmental settings.